Thyroid Hormones Accelerate Initiation of Skeletogenesis via MAPK (ERK1/2) in Larval Sea Urchins (Strongylocentrotus purpuratus) - Taylor, Elias; Heyland, Andreas (Frontiers in Endocrinology, 2018)
Thyroid hormones are important regulators of development and metabolism in animals. Their function via genomic and non-genomic actions is well established in vertebrate species but remains largely elusive among invertebrates. Previous work suggests that thyroid hormones, principally 3,5,3',5'-Tetraiodo-L-thyronine (T4), regulate development to metamorphosis in sea urchins. Here we show that thyroid hormones, including T4, 3,5,3′-triiodo-l-thyronine (T3), and 3,5-Diiodothyronine (T2) accelerate initiation of skeletogenesis in sea urchin gastrulae and pluteus larvae of the sea urchin Strongylocentrotus purpuratus, as measured by skeletal spicule formation. Furthermore, our investigation of TH mediated skeletogenesis shows that Ets1, a transcription factor controlling initiation of skeletogenesis, is a target of activated (phosphorylated) mitogen-activated protein kinase [MAPK; extracellular signal-regulated kinase 1/2 (ERK1/2)]. As well, we show that PD98059, an inhibitor of ERK1/2 MAPK signaling, prevents the T4 mediated acceleration of skeletogenesis and upregulation of Ets1. In contrast, SB203580, an inhibitor of p38 MAPK signaling, did not inhibit the effect of T4. Immunohistochemistry revealed that T4 causes phosphorylation of ERK1/2 in primary mesenchyme cells and the basal membrane of epithelial cells in the gastrula. Furthermore, pre-incubation of sea urchin gastrulae with RGD peptide, a competitive inhibitor of TH binding to integrins, inhibited the effect of T4 on skeletogenesis, as well as on ERK1/2 phosphorylation. Together, these experiments provide evidence that T4 acts via a MAPK- (ERK1/2) mediated integrin membrane receptor to accelerate skeletogenesis in sea urchin larvae. These findings shed light, for the first time, on a putative non-genomic pathway of TH action in a non-chordate deuterostome and help elucidate the evolutionary history of TH signaling in animals.